The Outcome of the Saving-Investment Discussion - Lutz, F. A. (Quarterly Journal of Economics, 1938)
Keynes I. Saving and investment may differ, 589.— Significance of the concepts as used here, 591.— Valueless for monetary policy, 594.— Robertson. The “day,” 595.— Consequences of this change, 597.— Applicable only under certain conditions, 598.— Similar concepts, 600.— The ex ante and ex post concepts. Myrdal, 602.— Usefulness of these concepts, 604.— Comparison with Robertson, 604.— Active and passive investment and saving, 607.— Keynes II. Saving always equals investment, 608.— Association with the multiplier, 608.— Comparison with classical view, 611.— Conclusions, 613.